ECOLOGICAL SITUATION OF REGION OF CARPATHIANS BUT ECOLOGICAL TOURISM - Міщенко, Л. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Analysis of natural terms of region of Carpathians of Ukraine as factors of forming of him ecological situation and geoekologichnogo state based on the association of mountain and pre-mountain territories, that conditioned by integrity of their structurally tectonic and geomorfologichnikh, climatic and hydrographical, floristichnikh and the geobotanical, zoogeographical, ground and landscape features. Geoekologichni researches on this territory have an important value for scientifically cognitive strategy of development and introduction of ekoturizmu.